The liver organoid’s past, present and future: a personalized medicine strategy - Abady, Mariam; Zahran, Ibrahim A; Elmokhtar, Yasmin (International journal of health sciences, 2024)
Organoids are three-dimensional (3D) cell culture systems derived from human pluripotent stem cells or organotypic differentiation, replicating the complex interactions and functionalities of actual organs. These systems offer significant advantages for studying human tissue and organ biology, addressing limitations of animal models related to sample accessibility and ethical concerns. Liver organoids, in particular, are advanced models developed to study hepatic phenotypes, encompassing various cell types and enabling detailed investigation of cellular, molecular, and genetic aspects of liver diseases, drug metabolism, and protein secretion. They hold promise for fundamental research, drug discovery, and regenerative medicine applications. Despite their potential, organoids face limitations such as simplicity, lack of high-fidelity cell types, flexibility, and atypical physiology. Enhancements in organotypic liver-like surrogates, incorporating in vivo-like cell interactions and architecture, along with advancements in microfluidic chip technology, are expected to improve models for disease, toxicity, and drug discovery, paving the way for new treatments. This review will provide an overview of the history and development of liver organoids, their current progress, challenges, applications, and future prospects in the field of personalized medicine.